Skupaj (University of Maribor Press, 2023)
50 years have passed since the publication of the collection Together, which was created in 1973 by Andrej Brvar, France Forstnerič, Drago Jančar, Marijan Kramberger and Tone Partljič with their literary works. It was a symbolic joint action of five literary creators and good friends who believed that quality literary creation can also be done outside the Slovenian cultural center, but it is necessary to overcome provincialism. Visually, conceptually and aesthetically, it was about diverse creators who, despite criticism, opposition and difficulties, persevered and took their own path. They proved that they were right, because with their works and activities they marked decades of cultural events in Slovenia until today. Maribor University Library dedicated an event to the 50th anniversary of the "Maribor Five" on the occasion of the Slovenian cultural holiday. We have prepared an exhibition, a conversation with the three surviving members of the five, and a screening of Zoran Bilodjerič Peteric’s documentary film, which was created in 2012 as part of the European Capital of Culture. On this occasion, the original version of the film will be transferred to the Maribor University Library fund with a donation from the author’s son, Jan Bilodjerič. The exhibition Together presents the joint performance of the five and their further creative paths. It is complemented by a selection from the legacies of Marijan Kramberger and France Forstnerič, which the University Library of Maribor acquired in the past years and which, together with the partial archive of Andrej Brvar, are included in the UKM Manuscript Collection. On this occasion, the set of exhibition catalogs is joined by the presentation of the five under the title Together. Care for the maintenance and preservation of the domestic cultural heritage remains a permanent feature of the Maribor University Library.